2017
DOI: 10.1097/md.0000000000006417
|View full text |Cite
|
Sign up to set email alerts
|

micro-RNA screening and prediction model construction for diagnosis of salt-sensitive essential hypertension

Abstract: Commonly used tests for diagnosis of salt-sensitive hypertension (SSH) are complex and time-consuming, so new methods are required. Many studies have demonstrated roles for miRNAs in hypertension; however, the diagnostic value of miRNAs has yet to be determined for human SSH. In this study, we examined miRNA expression profiles by initial high-throughput miRNA sequencing of samples from patients with salt-sensitive and salt-resistant hypertension (SSH and SRH, respectively; n = 6, both groups), followed by val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…miR-4516, intronic to the PKD1 gene locus, was the only miRNA that was higher in salt-sensitive patients and lower in inverse salt-sensitive patients compared with controls. Qi et al (88) used whole blood and qPCR to screen potential miRNAs as biomarkers for salt sensitivity in 91 participants. Their strongest signal was for miR-361-5p, which was associated with the risk of salt sensitivity.…”
Section: Mirna Biomarkers In Hypertensionmentioning
confidence: 99%
“…miR-4516, intronic to the PKD1 gene locus, was the only miRNA that was higher in salt-sensitive patients and lower in inverse salt-sensitive patients compared with controls. Qi et al (88) used whole blood and qPCR to screen potential miRNAs as biomarkers for salt sensitivity in 91 participants. Their strongest signal was for miR-361-5p, which was associated with the risk of salt sensitivity.…”
Section: Mirna Biomarkers In Hypertensionmentioning
confidence: 99%
“…Exhilaratingly, one study found for the first time that plasma miR‐30a and miR‐29 in white‐coat hypertension (WCH) patients are significantly higher while plasma miR‐133 in WCH patients is lower than hypertension patients and healthy controls, indicating that plasma miR‐30a, miR‐29 and miR‐133 have promising clinical values as biomarkers for identifying WCH patients from hypertension patients and normotensive individuals 180. Moreover, whole blood miR‐361‐5p and miR‐362‐5p are reduced in salt‐sensitive hypertension (SSH) compared with salt‐resistant hypertension (SSR) 181. This helps to develop a flexible, non‐invasive SSH diagnostic method that can avoid the previous tests with complex procedures.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 99%
“…Recent studies demonstrated that numerous miRNAs were involved in the development of hypertension by mediating vascular remodeling and injury of the heart, kidney and other organs (19,20). For instance, miR-122 induced endothelial NO metabolic disorder and disrupted diastolic and contractile function of the vascular endothelium by targeting solute carrier family 7 member 1, leading to the development of primary hypertension (21).…”
Section: Discussionmentioning
confidence: 99%